Portable tunable interband cascade laser spectrometer using thin-film waveguides for food contaminant analysis - A. Femenias; M. Erdem; P. Fomina; J. Scheuermann; U. Blazhko; S. Freitag; A. J. Bosman; R. Weih; J. Koeth; A. Kohler; R. Krska; G. I. J. Salentijn; et al. (AIP Advances, 2024)
Interband cascade lasers (ICL) are high output power mid-infrared light sources with low power consumption, serving as a viable alternative to more commonly applied quantum cascade lasers. The integration of ICLs with thin-film waveguides facilitates miniaturized sensing platforms based on the principles of evanescent field absorption toward tailorable high-fidelity portable mid-infrared (MIR) sensing solutions for on-site chemical analysis. The analytical performance of a MIR sensing system is presented combining a tunable interband cascade laser emitting at a wavelength range of 5.88–6.09 µm (1702–1641 cm−1) with a 6 µm GaAs/AlGaAs thin-film waveguide as the active transducer for customized evanescent field absorption analysis of food contaminants. A comparison of the analytical performance of the developed tICL-based system vs conventional Fourier-transform infrared spectroscopy is presented for the exemplary analysis of the Fusarium mycotoxin deoxynivalenol, a persistent food contaminant resulting from fungal infection. The thin-film waveguide enhances the sensitivity compared to conventional attenuated total reflection systems, revealing improved detection limits. The compact design of the system, along with the favorable analytical figures-of-merit and automated data processing, confirm the potential of the developed tICL-based spectrometer for on-site detection of food contaminants at various stages along the food supply chain.